2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-4.13965
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics and expression of adhesion markers in cells of low differentiated endometrial carcinoma

Abstract: Summary. The aim of the study was to evaluate the morphological features of endometrioid carcinoma of the endometrium (ECE) of low differentiation grade with different invasive potential and to characterize their molecular phenotype by the expression of a number of adhesion markers. Materials and Methods: We have studied the samples of operation material of 37 patients with ECE of low differentiation grade with deep invasion (> ½ myometrium), n = 26, and with invasion < ½ myometrium, n = 11, with the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Such ECEs often had large, convoluted glands, tightly surrounding the myometrium, and "invasive front areas". As it was shown in the authors' previous study while investigating the morphological traits of such neoplasms, they invaded the myometrium by large groups of tumour cells in the form of solid bands which is a morphological manifestation of collective migration [17]. These results agree with the data of other researchers who demonstrated that such morphological traits of ECE are associated with the decreased expression of EMT markers [29,30].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Such ECEs often had large, convoluted glands, tightly surrounding the myometrium, and "invasive front areas". As it was shown in the authors' previous study while investigating the morphological traits of such neoplasms, they invaded the myometrium by large groups of tumour cells in the form of solid bands which is a morphological manifestation of collective migration [17]. These results agree with the data of other researchers who demonstrated that such morphological traits of ECE are associated with the decreased expression of EMT markers [29,30].…”
Section: Resultssupporting
confidence: 89%
“…The data obtained were compared with the results of the previous studies, in which the authors determined the expression of EMT markers in these very cases of ECE [16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…Expression of all immunohistochemical markers (β-catenin, Dkk1, E-cadherin and N-cadherin) was evaluated by counting the number of immuno-positive tumor cells and expressed by percentage. Tumor cells were deemed positive if there was a clear membranous (β-catenin) ( 36 , 37 ), membranous and/or cytoplasmic (E-cadherin, N-cadherin) ( 29 , 38 ) and cytoplasmic (Dkk1) ( 10 , 39 , 40 ) reaction. At the same time, intensity of reaction was scored on the scale from 0 to 3 (0 = no reaction, 1 = mild, 2 = moderate, 3 = strong).…”
Section: Methodsmentioning
confidence: 99%
“…Florescu et al found significant differences between intensity of membranous β -catenin immunopositivity and degree of tumour differentiation, invasion in the myometrium and tumour stage [ 40 ]. Such findings suggest that decreased expression of β -catenin, characteristic of EMT, could also be determined by IHC methods [ 13 , 40 ]. Machin et al found a correlation between exon 3 mutations of CTNNB1 and nuclear β -catenin immunostaining [ 48 ]; thus, more recent studies tried to validate IHC methods as a surrogate for identification of exon 3 mutations in CTNNB1 [ 44 , 46 , 49 ].…”
Section: Immunohistochemical Methods For Detection Of Ctnnb...mentioning
confidence: 99%
“…Most endometrioid tumours have few somatic copy-number alterations (SCNAs) whereas most serous and serous-like tumours exhibit extensive SCNAs, and the extent of SCNA roughly correlates with progression-free survival [ 12 ]. However, there is substantial variability in the clinical course of the disease, associated with both morphological and molecular features of the tumour [ 13 ].…”
Section: Molecular Classification Of Ecmentioning
confidence: 99%